Studi Kasus Pencemaran Sampah dan Pengelolaan Sampah di TPA Supit Urang Malang - Diartika, Eka Imbia Agus; Sueb, Sueb (Jurnal Pembangunan Wilayah dan Kota, 2021)
The waste problem is crucial. With the increase in the amount of waste in Indonesia, research on the phenomenon of the amount of waste and the pollution it causes becomes an interesting matter, especially in urban areas, such as in the TPA of Malang City. The disposal of waste in Malang is concentrated in TPA Supit Urang Malang. The purposes of this study were to determineÂ  waste pollution and waste management at Supit Urang Landfill Malang. This type of research was qualitative, used the case study method. Data collection techniques were laboratory tests, interviews, observation, and documentation. Data analysis technique used qualitative data analysis consisting of 3 stages, namely data condensation, data display, and drawing and verifying conclusions. The results of this study were the amount of waste at Supit Urang Landfill Malang continued to increase and the pollutions also increased due to leachate originating from waste. Waste management at Supit Urang Malang Landfill started from separating organic and inorganic waste. Organic waste was processed into fertilizer, while inorganic waste was collected in a waste bank for sale.Â